Technology and Architecture for a System of High-Speed Sensor Data Stream Collection and Processing - V. Kopytov, Vladimir; V. Kharechki, Pavel; V. Naumenko, Vladimir; V. Savartsov, Aleksey; V. Dorofeyev, Oleg; V. Batashan, Mikhail (International Journal of Engineering and Technology, 2018)
Objective: The objective is to address the challenges of monitoring process facility and environmental parameters, which can be analyzed to anticipate dangerous and critical conditions.Methodology/approach: This article proposes the technology and architecture for a system of high-speed stream data collection and processing, which combines the advantages of both the cloud and fog computing models for data collection, storage and processing.Conclusion: The proposed technology and architecture for a system of high-speed stream data collection and processing make it possible to adapt to various monitoring and situation control challenges and can be used to set up centers for processing monitoring data of different levels.Originality/value: The originality of the proposed technology and architecture consists in the application of a set of universal programming solutions aiming to set up a data processing center. Such a center would require a minimum amount of work related to designing an automated data collection system and to developing additional software. Furthermore, it will provide ample opportunities for further scaling and expanding its functionality.Â Â